Transposition glabellar flap in post orbital exenteration fistula: case report - Munjal, Manish; Munjal, Shubham; Verma, Ritesh; Sharma, Salony; Arora, Vineeta; Kaur, Hardeep; Chawla, Deeksha; Sandhu, Loveleen; Kaur, Gursimran; ., Utkarsh; Singh, Diljot (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Reconstruction of facial orbital region defects, secondary to wound dehiscence following orbital exentration to treat Mucormycosis is an issue confronting the rhinologist. The transposition flaps have a vital role when expected result is unlikely, neither aesthetic nor functional, with a simple primary closure, secondary intention, advancement sliding flap or by free skin grafts. Glabellar transposition flap was used in a patient with a wide defect involving the medial wall of the orbit. Though there is a delicate dissection of pedicel there is likelihood of a trapdoor deformity but the glabellar flap facilitates repair in a single-staged procedure. Moreover, the donor site scars are merged in the margins of the aesthetic units thereby retaining facial cosmesis.